The Internet of Things and Its Impact on The Productivity And Economic Growth of The Manufacturing Industry - Soni Suardi; Pudji Astuty (Jurnal Indonesia Sosial Sains, 2023)
At a practical level, IoT is a network in which all physical objects connect to the internet via network devices or routers and transfer data. IoT allows objects to be controlled remotely through the existing network infrastructure. The existence of IoT is considered to make it easier for humans to do their work. One of the factors affected by IoT is productivity. Productivity referred to here is work productivity, and its impact on increasing sales, which is related to the economic growth of the manufacturing industry. The influence of IoT, whether we like it or not, will impact all sectors of life. The Internet of Things is slowly turning from a vision to a reality. The IoT platform plays a central role in evolution by providing many architectural blocks. IoT also has the potential to increase the availability of information and is likely to transform companies and organizations in almost every industry in the world. Thus, in the future, economic developments will be able to be monitored and predicted based on an IoT platform that is tailored to the needs of each industry, as well as the goals of the company